A Fully Distributed Economic Dispatch Method in DC Microgrid Based on Consensus Algorithm - Liu, Dan; Jiang, Kezheng; Yan, Linfang; Ji, Xiaotong; Cao, Kan; Xiong, Ping (IEEE access, 2022)
Uncertainties of intermittent renewables and complexities of load demands bring challenges to the optimal operation of the microgrid. This paper proposes a fully distributed method based on the consensus algorithm for solving the economic dispatch problem (EDP) of DC microgrids. The proposed distributed method is performed using a multiagent system. It only needs information from neighboring agents and does not need a central controller. A two-level control structure is adopted to realize the economic dispatch and voltage regulation simultaneously. The upper level obtains the optimal power reference of dispatchable agents and maintains the power balance of the system. The lower level performs an improved droop control to track the power reference and regulate the average bus voltage for the microgrid. The proposed method's properties and convergence are analyzed using eigenvalue perturbation theory to obtain a faster convergence speed. By designing the adjacency matrix appropriately, the proposed method can ensure the system stable when the communication topology changes. Finally, several simulations are designed to verify the effectiveness of this novel control method.